(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
The utilization of various contemporary analytical methods has become indispensable when it comes to assessing polyherbal Ayurvedic formulations, aiming to ensure their quality, safety, and effectiveness. Quality control of herbal medicines involve analytical evaluation using instrumental techniques such as TLC, HPTLC, HPLC, GC-MS, LC-MS and spectrophotometer etc. Among them Liquid Chromatography with tandem Mass Spectrometry (LC-MS/MS) is a powerful hyphenated analytical technique that combines the separating power of liquid chromatography with the mass analysis capabilities of mass spectrometry. Generally, its application is oriented towards the specific detection and potential identification of chemicals in a complex mixture. Polyphenolic compounds are usually referred to as a diverse group of naturally occurring compounds containing multiple phenolic functionalities. The anti-inflammatory, anti-aging, antiproliferative, and antioxidant like biological properties of phenolic compounds have been described in several studies. This research study was taken to analyse polyphenolic compounds in Guduchyadi kashaya by LC-MS/MS. Phenolic compounds are abundant in the ingredients of Guduchyadi kashaya, as evidenced by previous studies. So, to determine the polyphenolic contents of Guduchyadi kashaya, this study was conducted. The quantification of the polyphenols was carried out on Shimadzu Shim Pack GISS C18 column with .1%formic acid as mobile phase. A total of 28 polyphenolic compounds were analysed, and 24 of these compounds were found to be present in Guduchyadi kashaya. The results showed that the phenolic compounds present in the ingredients were also present in the formulation in high abundance.